2023
DOI: 10.1002/pol.20230403
|View full text |Cite
|
Sign up to set email alerts
|

pH‐responsive polymers for drug delivery: Trends and opportunities

Jagtar Singh,
Pallavi Nayak

Abstract: Polymer science has applications in biomedical engineering, prosthetics, surgical implants, and prospective pharmaceutical excipients for drug delivery. “Intelligent or Smart Polymers” are created for drug targeting either by derivatization of natural polymers or controlled radical polymerization of electrolytes. Their mode of action is governed by the environmental stimuli viz. temperature, pH, ionic concentration, magnetism, and so on. pH‐responsive polymers, because of their self‐assembling behavior, alter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 205 publications
0
8
0
Order By: Relevance
“…For the pK a value of polymerized MAA, a value of 4.8 was reported by Singh and Nayak. 13 Buback et al 52 explain the difference in pK a value of the polymerized MAA due to the "exchange of hydrogen cations as well as counterions during polymerization". For the kinetic model of the NIPAM−BIS− MAA synthesis in this work, we consider the change in pK a as negligible as the resulting model is insensitive to changes in the pK a parameter values.…”
Section: Industrial and Engineeringmentioning
confidence: 99%
See 2 more Smart Citations
“…For the pK a value of polymerized MAA, a value of 4.8 was reported by Singh and Nayak. 13 Buback et al 52 explain the difference in pK a value of the polymerized MAA due to the "exchange of hydrogen cations as well as counterions during polymerization". For the kinetic model of the NIPAM−BIS− MAA synthesis in this work, we consider the change in pK a as negligible as the resulting model is insensitive to changes in the pK a parameter values.…”
Section: Industrial and Engineeringmentioning
confidence: 99%
“…Previously, it was found that the p K a value changes during the polymerization of MAA. For the p K a value of polymerized MAA, a value of 4.8 was reported by Singh and Nayak . Buback et al explain the difference in p K a value of the polymerized MAA due to the “exchange of hydrogen cations as well as counterions during polymerization”.…”
Section: Dynamic Model Of Charged Microgel Synthesis and Parameter De...mentioning
confidence: 99%
See 1 more Smart Citation
“…pH-Responsive polymers possess the unique ability to undergo conformational changes or alterations in hydrophilicity in response to local pH conditions. 20,21 This characteristic is harnessed to prevent premature drug release, taking advantage of the pH disparity between healthy and cancerous tissues. 22,23 In our previous investigations, we successfully synthesized MSNs coated with poly(2-(diethylamino)ethyl methacrylate) as pore caps, enabling the loading of DOX.…”
Section: Introductionmentioning
confidence: 99%
“…Intelligent/responsive polymers have attracted a significant surge of attention over the past few decades due to their capability to respond to single or multiple chemical and/or physical stimuli, and a great deal of research has been devoted to creating environmentally responsive large molecules that can be transformed into innovative smart materials. , These materials have found extensive applications in fields like controlled drug release, artificial muscles, and medical devices and biosensors . More recently, multiresponsive polymers have gained popularity due to their multidimensional responses, which improve their sensitivity and specificity .…”
Section: Introductionmentioning
confidence: 99%